Prevalence of Polycystic Ovarian Syndrome in Alkhoms City, Libya: A Cross-sectional study - Alhmmali Abdalla; Randa Alzowam; Dalal Alkilani; Turkia Altwer (AlQalam Journal of Medical and Applied Sciences, 2025)
Polycystic Ovarian Syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age. This study investigates the prevalence of PCOS, focusing on patient-related and disease-related factors. A cross-sectional survey was conducted to explore obstetricians’ and gynecologists’ perspectives on the diagnosis, prevalence, and management of PCOS. A total of 35 specialists, each with at least three years of clinical experience, participated. The survey included open-ended questions covering patient-related factors (e.g., symptoms, lifestyle) and disease-related aspects (e.g., prevalence, diagnostic methods, treatment). Data were collected through face-to-face interviews from January to April 2022, ensuring confidentiality and standardized procedures to minimize bias. This study analyzed PCOS’s prevalence, etiology, symptoms, diagnosis, and treatment. The highest prevalence (62.9%) was observed in the 20–29 age group, declining with age. Unknown causes accounted for 51.42% of cases, followed by hormonal and genetic factors (41.42% each). Menstrual irregularity (80%) was the most common symptom. Ultrasound was the primary diagnostic tool (82.85%), while metformin was the most prescribed treatment (71.42%). PCOS was the most prevalent condition among gynecological disorders (57.14%). These findings highlight the significant burden of PCOS and the need for improved management strategies. Our study concluded that the PCOS remains a significant health concern both globally and within Libya. Highlights the necessity for heightened awareness, early screening, and tailored management strategies. Further research is warranted to explore the underlying causes of regional prevalence variations and to develop culturally appropriate interventions that address the unique needs of the Libyan female population. تُعد متلازمة تكيس المبايض من أكثر الاضطرابات الغددية شيوعًا التي تصيب النساء في سن الإنجاب. تهدف هذه الدراسة إلى معرفة معدل انتشار متلازمة تكيس المبايض، مع التركيز على العوامل المتعلقة بالمرضى والمرض نفسه. أُجريت دراسة مقطعية لاستكشاف آراء أطباء النساء والولادة حول تشخيص متلازمة تكيس المبايض ومدى انتشارها وطرق علاجها. شارك في الدراسة 35 طبيبًا متخصصًا، يتمتع كل منهم بخبرة سريرية لا تقل عن ثلاث سنوات. شمل الاستبيان أسئلة مفتوحة تناولت العوامل المتعلقة بالمرضى (مثل الأعراض ونمط الحياة) والجوانب المتعلقة بالمرض (مثل معدل الانتشار، وطرق التشخيص، والعلاج). تم جمع البيانات من خلال مقابلات مباشرة خلال الفترة من يناير إلى أبريل 2022، مع ضمان السرية واتباع الإجراءات القانونية. وضحت هذه الدراسة معدل انتشار متلازمة تكيس المبايض وأسبابها وأعراضها وطرق تشخيصها وعلاجها. وُجد أن الفئة العمرية 20-29 عامًا سجلت أعلى نسبة انتشار (62.9%)، مع تناقص النسبة مع تقدم العمر. وكانت الأسباب غير معروفة في 51.42% من الاستبيانات، تلتها العوامل الهرمونية والوراثية (بنسبة 41.42% لكل منهما). كانت اضطرابات الدورة الشهرية أكثر الأعراض شيوعًا (80%). وكان الفحص بالموجات فوق الصوتية هو الأداة التشخيصية الأساسية (82.85%)، بينما كان الميتفورمين العلاج الأكثر وصفًا (71.42%). كما تبين أن متلازمة تكيس المبايض هي الاضطراب الأكثر انتشارًا بين أمراض النساء (57.14%). تؤكد هذه النتائج المشاكل الكبيرة الذي تسببها متلازمة تكيس المبايض، مما يستدعي تطوير استراتيجيات محسنة للتشخيص والعلاج. خلصت هذه الدراسة إلى أن متلازمة تكيس المبايض لا تزال تشكل مصدر قلق صحي كبير، سواء على المستوى العالمي أو في ليبيا. وتؤكد هذه النتائج الحاجة إلى زيادة الوعي، وتعزيز الفحوصات المبكرة، وتطوير استراتيجيات علاجية مخصصة. كما أن هناك حاجة لإجراء المزيد من البحوث لاستكشاف الأسباب الكامنة وراء التباينات الإقليمية في معدل الانتشار